Analytical investigations on free vibration response of ferrocement plates - Arif, Mohammad; Ahmad, Tazyeen; Shariq, Mohammad; Ibadurrahman (Journal of Structural Engineering, 2024)
The present investigation aims at studying the effect of support conditions, moduli ratio and mesh orientation on free flexural vibration response of ferrocement plates. A test slab of size 838.2 × 838.2 × 24.12 mm has been considered. The finite element analysis uses a ninenoded Lagrangian element employing both consistent and lumped mass formulations. The rigidities are evaluated by using laminated plate theory incorporating Mindlin approach. The moduli ratio (E11/E22) is varied as 1,10, 40 and the orientation is varied as 0°, 15°, 30° and 45°. Four supports arrangements viz. (i) all edges clamped (C-C-C-C), (ii) three edges clamped and one edge simply supported (C-C-C-S), (iii) two opposite edges clamped and other two edges simply supported (C-S-C-S) and (iv) one edge clamped and three edges simply supported (C-S-S-S). The highest frequency is observed for C-C-C-C plate and lowest for C-S-S-S plate. Under isotropic situation (E₁₁/E₂₂=1), for C-C-C-C plate, the highest fundamental frequency is found with 0° orientation and lowest with 45° orientation. For C-C-C-S, C-S-C-S and C-S-S-S plates, highest fundamental frequency is observed at 45° orientation and lowest at 0° orientation. When moduli ratio is 10 or 40, the highest fundamental frequency is observed at 45° orientation and lowest at 0° orientation for all plates except C-S-S-S plate, which imparts highest frequency at 0° orientation and lowest at 45° orientation. The mode shapes and contours of zero lateral deflection have been drawn.